'Get out of my fandom, newbie': A cross-fandom study of elitism and gatekeeping in fans. (1st June 2020) - Plante, Courtney N.; Reysen, Stephen; Chadborn, Daniel; Roberts, Sharon E.; Gerbasi, Kathleen C.
In the present article we discuss three studies aimed at better understanding elitism in the context of fan groups. The studies assess different facets of elitism, predictors of elitism and the potential outcomes associated with holding elitist beliefs. The survey studies were conducted on members of three distinct fan groups: furries (fans of media featuring anthropomorphized animal characters), bronies (adult fans of the television series My Little Pony) and anime fans (fans of Japanese animation). Elitism was found to include both self-inflation and other-derogation and is predicted by two components of fan identity (fanship and fandom). Elitism was also significantly associated with pro-gatekeeping attitudes and behaviours. Practical and theoretical implications for fan culture are discussed. We also discuss the limitations of the studies and their ability to contribute to a discussion about creating inclusive fan spaces.